Pengaruh Model Pembelajaran Advokasi Terhadap Motivasi Belajar Pak Siswa Kelas IX SMP Swasta GBKP Kabanjahe Tahun Pembelajaran 2023/2024 - Mikel Ermadanna Tarigan; Rida Gultom; Masniar H. Sitorus; Nisma Simorangkir; Dorlan Naibaho (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
The aim of this research is to determine the effect of the advocacy learning model on the PAK learning motivation of class IX students at GBKP Kabanjahe Private Middle School in the 2023/2024 Academic Year, with the hypothesis that there is an influence of the advocacy learning model on the PAK learning motivation of class IX students at GBKP Kabanjahe Private Middle School in the 2023/2024 Academic Year. . With a population of all class IX of GBKP Kabanjahe Private Middle School who are Protestant Christians, totaling 85 people with a sample of 85 people, so this research is a population research. Data was collected using a closed questionnaire with 33 items compiled by the author based on variable indicators according to expert theory. The questionnaire was tested with 35 respondents from class IX students at Berastagi Joint Private Middle School. using a 35 question questionnaire and after being tested, the results of the validity of the questionnaire were found to have a value of rcount > rtable = 0.254-0.773 (there were 2 question items that had validity less than rtable 0.334, namely item number 11 and item number 35 so that the invalid questionnaire was discarded Thus, the valid questionnaire consists of 33 questions. And the reliability of the questionnaire test is at 0.910, the value is very strong and has been tested for validity and reliability. The results of data analysis show that there is an influence of the advocacy learning model on students' PAK learning motivation class IX Private Middle School GBKP Kabanjahe Academic Year 2023/2024. Using the relationship test, rcount > rtable is obtained, namely 0.623>0.213, with a significant relationship test tcount > ttable, namely 9.273>2.000, with the linear regression test Y ̂ = α+bx = 13.91. +0.661X. This equation shows that in a constant state of 13.91, for every addition of variable 38.8%. This means that Ho is rejected and Ha is accepted. The significant influence test with Fcount>Ftable (52.52>4.00) means that there is a positive and significant influence between the advocacy learning model on the PAK learning motivation of class IX students at GBKP Kabanjahe Private Middle School for the 2023/2024 academic year. This research suggests that teachers always use the advocacy learning model in the teaching and learning process, so that the motivation of class IX students at GBKP Kabanjahe Private Middle School, Kabanjahe, for the 2023/2024 academic year will be better.